2015
DOI: 10.1108/ijoa-03-2014-0747
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality of management practices in Palestinian hospitals

Abstract: Purpose – This paper aims to provide an assessment of the quality of management practices and implementation in hospitals operating in the West Bank of Palestine using the Malcolm Baldrige National Quality Award (MBNQA) Criteria. Design/methodology/approach – Based on the MBNQA Criteria, a survey of 51 hospitals was conducted using questionnaires, interviews and focus groups to gather data. Data were analyzed and compared across all admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…On average hospitals consumed about 36 % of current health expenditures (CHE) during the period 2000–2011. However, governmental hospitals consumed about 60 % of MOH budget, yet inferior to private hospitals in terms of efficiency and quality [ 4 ]. In most OECD countries, hospitals also accounted for the highest share of CHE, on average (36 %), ranging from 26 % in Slovakia to 45 % in Denmark.…”
Section: Introductionmentioning
confidence: 99%
“…On average hospitals consumed about 36 % of current health expenditures (CHE) during the period 2000–2011. However, governmental hospitals consumed about 60 % of MOH budget, yet inferior to private hospitals in terms of efficiency and quality [ 4 ]. In most OECD countries, hospitals also accounted for the highest share of CHE, on average (36 %), ranging from 26 % in Slovakia to 45 % in Denmark.…”
Section: Introductionmentioning
confidence: 99%
“…Karamat et al (2019) investigated 19 drivers of knowledge management adoption in public and private hospitals of Pakistan and developed a hierarchical structure using ISM to understand sustainability in healthcare sector. Sabella et al (2015) assessed the QM practices and implementation in hospitals operating in the West Bank of Palestine using the Malcolm Baldrige National Quality Award model criteria and found that the hospitals of the area exhibited concern on human resource focus, information and analysis and performance results. Zarei et al (2018) assessed the quality management system status using QM system index in Iranian public and non-public hospitals and observed the difference between them was significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the face of these facts with regard to the present state of healthcare quality in India, concepts like clinical governance, healthcare audit, healthcare effectiveness, peer reviews, healthcare accreditation and continuous professional development skills are examples that are proposed to monitor and improve the quality of healthcare services. Furthermore, several healthcare establishments (HCEs) adopted various industrial quality management (QM) concepts and strategies like continuous quality improvement (CQI), Six Sigma, quality assurance, quality function deployment, Machine Learning, Big Data Analytics and total quality management (TQM) to improve the quality of services in healthcare (Sabella et al , 2015; Talib et al , 2011; Mosadeghrad, 2015). TQM has gained wide popularity across the globe, predominantly in developed countries (Sabella et al , 2015; Calvo-Mora et al , 2014; Chavez et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations